Perspectives on ancestral lineages and genetic markers of Malay population in Peninsular Malaysia - Shalini Parthipan,; Seri Mirianti Ishar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Malay people are the majority in Peninsular Malaysia, but their population structure and genetic profile remain poorly studied. The exposure to the origins of Malays and their sub-ethnic groups is vital prior to study about their genetic profiles as it can narrow down the haplogroups of their ancestral lineages. In this review, we have highlighted theories related to the origin of Malays from Yunnan, New Guinea, Taiwan, Sundaland, Nusantara and the theory of Bani Jawi. Nevertheless, these theories were established based on speculations without evidence. Despite the theories developed, the migration of Malay population is more prominent during the era of Malacca Sultanate. The trading activities and seafaring way of life had welcomed various ethnic groups in Peninsular Malaysia which formed a part of the Malay population today. Thus, the origin of major sub-ethnic groups of Malay population are discussed in this paper. The origin of Malay community has a key relationship with modern genomic field that was conducted through mitochondrial DNA analysis. Human identification in forensic application is tedious due to the need for sequencing whole DNA profile of Malay population. Therefore, identification of specific genetic markers for Malay population is vital to facilitate forensic investigation. We gathered data by systematically searched with Google Scholar, Pubmed, Science Direct with advanced search builder for papers titles with Malay population and genetic markers. This study shed some light on the mitochondrial DNA markers of indigenous people and Malay population in Peninsular Malaysia which can be used in future prospects.